Exploring Friendship Experiences among Incarcerated and Formerly Incarcerated Women: A Qualitative Interpretative Meta-Synthesis - Patel, Mansi (Women & criminal justice, 2022)
Although incarceration of women in the United States is at a historic high, the understanding of women’s experiences in prison and how this time affects their lives after prison is very limited. Qualitative studies of this population are crucial for practice and research and as more qualitative research is conducted; the challenge will be to develop ways to synthesize the findings for policy application. The purpose of this qualitative interpretive meta-synthesis was to understand how women experience friendship in a carceral setting and the implications of these relationships. The synthesis revealed one overarching theme: belonging/acceptance and five subthemes: similar life experiences enrich a friendship, low self-esteem can affect the ability to form friendships in justice involved women, it is hard for justice involved women to trust people, justice involved women have anxiety surround reintegration that friendships can help mitigate, and friendships are an effective means to cope with incarceration.